1980
DOI: 10.3382/ps.0590352
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Protein during the Pre-Breeder Period on Subsequent Reproductive Performance of Large White Turkeys

Abstract: Large White female turkeys of a commercial variety were used to determine the effects of low dietary protein during the pre-breeder period (12 to 32 weeks of age) on subsequent reproductive performance. Diets containing 10, 12, 14, and 17% protein were fed from 12 weeks or 20 weeks to 32 weeks of age. At 32 weeks of age, all females were fed a 17% protein breeder diet. Reproductive performance was measured for a 24-week production period. Pre-breeder feed consumption and body weight gain from 12 to 32 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…During the first egg production season, turkey hens fed ad libitum during the growth, holding, and reproductive phases have been reported to either lose (Borron et al, 1974;Cherms et al, 1976;Thomason et al, 1976;McCartney et al, 1977;Krueger et al, 1978;Potter et al, 1978;Menge et al, 1979;Owings and Sell, 1980;Rosebrough et al, 1980) or gain body weight (Balloun, 1974;Borron et al, 1974;Woodard et al, 1974;Andrews and Morrow, 1978;Meyer et al, 1980;Rosebrough et al, 1980;Nestor et al, 1981) during the reproductive period. Following a forced molting, a gain (Ferguson et al, 1975) or loss in body weight (Thomason et al, 1976) has been reported during the second production period.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the first egg production season, turkey hens fed ad libitum during the growth, holding, and reproductive phases have been reported to either lose (Borron et al, 1974;Cherms et al, 1976;Thomason et al, 1976;McCartney et al, 1977;Krueger et al, 1978;Potter et al, 1978;Menge et al, 1979;Owings and Sell, 1980;Rosebrough et al, 1980) or gain body weight (Balloun, 1974;Borron et al, 1974;Woodard et al, 1974;Andrews and Morrow, 1978;Meyer et al, 1980;Rosebrough et al, 1980;Nestor et al, 1981) during the reproductive period. Following a forced molting, a gain (Ferguson et al, 1975) or loss in body weight (Thomason et al, 1976) has been reported during the second production period.…”
Section: Introductionmentioning
confidence: 99%
“…Flocks housed in conventional floor pens which initiate egg production in cool weather and continue egg production into hot weather (seasonal flocks) normally lose weight during the reproductive period (Cherms et al, 1976;McCartney et al, 1977;Potter et al, 1978;Owings and Sell, 1980). Conversely, flocks housed in conventional floor pens which initiate egg production in warm or hot weather and continue egg production into cool weather (out of season flocks) gain weight during the reproductive period (Meyer et al, 1980) or maintain relatively constant weight (Krueger et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer et al (1980aMeyer et al ( , 1980b reported in adult turkeys that the low level of protein intake during the pre-breeding period affected negatively the egg production while spermatozoa concentration was not affected. Also, Hipes and Hepp (1995) referred that females depend entirely on exogenous sources of protein to satisfy the protein requirements of clutch production while the use of nutrient reserves by males may help them meet their reproductive commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Meyer et al (1977) also reported significantly reduced egg production but it was during the latter phases of the laying cycle with hens that had received 10 or 12% protein diets from 12 through 32 weeks of age.…”
Section: Introductionmentioning
confidence: 98%